Synopsis: Who influences government spending in agriculture? The roles of public actors in subnational funding allocation in Nigeria - Olofinbiyi, Tolulope; Mogues, Tewodaj (International Food Policy Research Institute, 2016)
A large body of evidence has focused on the drivers of agricultural policymaking in both developed- and developing-country settings. However, several applicable theories and empirical analyses on the dynamics of policymaking have not yet been applied to public expenditure decision-making in agriculture, particularly in Africa. The NSSP Working Paper on which this Policy Note is based makes a contribution to this literature by drawing on the framework of actor-centered institutionalism (Scharpf 1997) to understand the drivers of public agricultural expenditures in Nigeria. Actor-centered institutionalism provides a set of conceptual tools useful for understanding the dynamics of complex policy processes that take place among various actors within an institutional setting. Using this framework, we empirically examine how political and budget institutions affect the incentives of actors involved in the public agricultural finance process at subnational level in Nigeria, structures the interactions between them, and ultimately shapes expenditure al-locations. In this study, we employ a single-case, embedded case study strategy which involves multiple sub-units of analysis that is appropriate in the context of Nigeria’s complex federal and de-centralized structure.